(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
There are various answers to the question whether gender equality has been achieved in contemporary Serbian society. Some consider women to be absolutely equal, others think that the achieved equality has been lost; there are those who believe that it never existed and that it will be a long time before it is achieved. What could be the stubborn fact which would help us determine what the plausible answer is? Assuming that the presence of women in daily and weekly press reflects their social position, we shall attempt to discover how much and in what way women are present in Serbian papers. The research relies on corpus and computational linguistics and extraction of information. The analysis will be based on a corpus consisting of portions taken from daily papers and electronic media (Politika, Blic, Večernje novosti, Danas, B92) which have more than 600.000 words (collected 2009-2014) and a smaller extract from weekly press (Ilustrovana poltika, Bazar). The methods of computational linguistics will employ a comprehensive dictionary of the Serbian language and the extraction of information will be based on detecting the named entities with the help of grammars for shallow syntactic analysis. After evaluation, the obtained results will be examined in terms of quality and quantity.